Photocatalytic Oxidation of Triiodide in UVA-Exposed Dye-Sensitized Solar Cells - Matthew Carnie; Daniel Bryant; Trystan Watson; David Worsley (International Journal of Photoenergy)
UVA irradiation of glass mounted dye-sensitized solar cells without UV filtration causes failure within 400 hours of light exposure. The failure mode is shown to relate to consumption of I3−, which is directly related to TiO2 photo-catalysis. The onset of failure is easily determined from electrochemical impedance data where the recombination resistance of the TiO2/electrolyte back reaction drops markedly prior to the onset of degradation. At the point of complete cell failure this impedance value then dramatically increases as there is no longer an interfacial reaction possible between the TiO2 and the I3− depleted electrolyte. Device failure is most rapid for cells under electrical load indicating that the degradation of the electrolyte is related to photogenerated hole production by excitation of the TiO2. Once depleted by UV exposure, the I3− can be regenerated by simple application of a reverse bias which can restore severely UV degraded devices to near original working conditions.